Relationship between global identity and pro-environmental behavior and environmental concern: a systematic review - Pong, Vivien; Tam, Kim-Pong (Frontiers in Psychology, 2023)
Global issues such as environmental problems and climate change, require collective efforts. Global identity has been linked to the promotion of pro-environmental behavior by international and environmental organizations. In environment-related research, this all-inclusive social identity has been consistently related to pro-environmental behavior and environmental concern, but the underlying mechanisms are not well understood. This current systematic review seeks to examine past studies across disciplines that have reported findings on the relationship between global identity and the constructs of pro-environmental behavior and environmental concern and to synthesize findings on the potential pathways behind this relationship. Thirty articles were identified through a systematic search. We found that most studies reported a positive correlation, and the effect of global identity on pro-environmental behavior and environmental concern was stable across studies. Only nine of the studies empirically examined the underlying mechanisms of this relationship. Three major themes of these underlying mechanisms emerged: obligation, responsibility, and relevance. These mediators highlight the role of global identity in pro-environmental behavior and environmental concern via how individuals relate to other humans and how they appraise environmental problems. We also observed a heterogeneity in measurements of global identity and environment-related outcomes. As a topic of interest in multiple disciplines, a variety of global identity labels have been adopted, such as global identity, global social identity, humanity identity, Identification With All Humanity, global/world citizen, connectedness to humanity, global belonging, and psychological sense of global community. Self-report measures of behavior were common, but observations of actual behavior were rare. Knowledge gaps are identified, and future directions are suggested.